Thymomodulin enhances vaccination responses against Streptococcus agalactiae in Nile tilapia - Salvador, Rogério; Marcusso, Paulo Fernandes; Claudiano, Gustavo Silva; Marinho-Neto, Fausto Almeida; Yunis-Aguinaga, Jefferson; Ramos-Espinoza, Fernando Carlos; Cueva-Quiroz, Victor Alexander; Moraes, Julieta Rodini Engracia de (Revista de Ciências Agroveterinárias, 2022)
Streptococcosis caused by Streptococcus agalactiae is a major economic problem for Nile tilapia Oreochromis niloticus production worldwide. Inactivated vaccines are considered an efficient method for controlling streptococcosis. However, during the vaccination process, stress during fish handling could affect the immune response. Immunomodulators, such as thymomodulin, act on the immune system and can improve vaccination responses. Thus, the aim of this study was to assess the immunomodulatory effect of thymomodulin in O. niloticus vaccinated against S. agalactiae. For this, fish were distributed in a factorial design (2x2x6), corresponding to two levels of thymomodulin supplementation (0.0 and 0.3%), two treatments (sterile phosphate buffered saline and inactivated S. agalactiae vaccine). Initially, fish received thymomodulin supplementation for 30 days. Next, fish were vaccinated by injection intraperitoneal (i.p.) of heat inactivated S. agalactiae vaccine. 15 days after vaccination, all fish were challenged i.p. with S. agalactiae and blood samples were collected at 7, 14, 21 days post infection (DPI). Results revealed that fish supplemented with thymomodulin vaccinated or not developed better protection against S. agalactiae than vaccinated fish without thymomodulin. Furthermore, fish vaccinated and supplemented with thymomodulin presented high levels of antibodies after 14 and 21 DPI, suggesting that thymomodulin can promote the immune response in Nile tilapia.